Out of the box and onto Wall Street unorthodox insights on investments and the economy - Grant, Mark J., 1950-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2011)
"Out of the Box is part memoir and part investment strategy guide. Throughout his career, author Mark Grant has often taken a contrarian view. Rather than working on Wall Street or at the Chicago Mercantile Exchange, he's spent his time elsewhere on Main Street. He's very critical of all the "noise" in the markets which he feels leads investors to make poor choices in their holdings. He offers important rules perserving capital and making long-term profits"--
pt. 1. The wizard calls the ball -- pt. 2. Learning to dance until it moves -- pt. 3. Market issues -- pt. 4. The great game.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Global Financial Crisis, 2008-2009.; Finance -- History -- 21st century; Investment analysis; Electronic books